2016
DOI: 10.1016/j.ydbio.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic origin and lineage hierarchies of the neural progenitor subtypes building the zebrafish adult midbrain

Abstract: Neurogenesis in the post-embryonic vertebrate brain varies in extent and efficiency between species and brain territories. Distinct neurogenesis modes may account for this diversity, and several neural progenitor subtypes, radial glial cells (RG) and neuroepithelial progenitors (NE), have been identified in the adult zebrafish brain. The neurogenic sequences issued from these progenitors, and their contribution to brain construction, remain incompletely understood. Here we use genetic tracing techniques based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 44 publications
3
60
0
Order By: Relevance
“…In the adult telencephalon, radial glia (RG) operate as neural stem cells in both physiological and regenerative conditions and Notch and FGF signaling have been reported to control the ability of RG to generate new neurons in both conditions (Ganz, Kaslin, Hochmann, Freudenreich, & Brand, ; Kishimoto, Shimizu, & Sawamoto, ). However, few studies have examined other parts of the brain, such as the olfactory bulb, optic tectum, and cerebellum (Galant et al, ; Kaslin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the adult telencephalon, radial glia (RG) operate as neural stem cells in both physiological and regenerative conditions and Notch and FGF signaling have been reported to control the ability of RG to generate new neurons in both conditions (Ganz, Kaslin, Hochmann, Freudenreich, & Brand, ; Kishimoto, Shimizu, & Sawamoto, ). However, few studies have examined other parts of the brain, such as the olfactory bulb, optic tectum, and cerebellum (Galant et al, ; Kaslin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Optic tectum of adult zebrafish has two neuronal stem cell populations, NE and RG (Ito, Tanaka, Okamoto, & Ohshima, ). In post‐embryonic phase including adult stage, NE in tectal proliferation zone (TPZ) and her5‐positive NE in peripheral midbrain layer (PML) generate both neurons and RG in periventricular gray zone (PGZ) under physiological condition (Galant et al, ; Ito et al, ). Most of RG are, however, quiescent in physiological condition.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sections through the posterior tectum reveal that at this neuroanatomical level (yellow line), a larger domain of EdU + NE progenitor cells can be identified ( Fig. 1e; dashed lines), from which the tectal NE lineage and RG cells are derived (Galant et al, 2016). These distinctive stem/progenitor niches within the adult optic tectum provide an exceptional experimental system to investigate how each population ( Fig.…”
Section: The Adult Optic Tectum Contains An Isolated Population Of Nomentioning
confidence: 96%
“…Embryonically these cells are derived from slow-amplifying progenitors (Recher et al, 2013). Recently it has been demonstrated that these NE-Ap are the final progenitor phenotype of a well-defined NE lineage that originate from Her5-positive NE stem cells in the posterior tectum (Galant et al, 2016). Moreover, recent evidence suggests that NE cells of the zebrafish tectum rely on Wnt/β-catenin signalling to promote stem cell proliferation towards a neuronal phenotype (Shitasako et al, 2017), similar to the role of Wnt in the adult mammalian stem cell niches (Adachi et al, 2007;Jang et al, 2013;Seib et al, 2013).…”
Section: Introductionmentioning
confidence: 99%